2018
DOI: 10.20450/mjcce.2018.1371
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of biologically active amide derivatives of naphthenic acids under neat conditions

Abstract: Within the field of green chemistry, a noticeable results were obtained in the solvent-free synthesis of amide derivatives of naphthenic acids under microwave irradiation. Naphthenic acid amides, anilides, and morpholides were synthesized directly from free carboxylic acids and amines in the absence of solvent and catalyst under high-temperature heating in a closed-vessel system of microwave reactor. With this new and efficient method, different primary, secondary, and tertiary amide derivatives of naphthenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Biological studies on the recently synthesized sulfones have revealed their antifungal (Xu et al, 2011), antiparasitic (Kerr et al, 2009), antimicrobial (Patil et al, 2010), antiviral (La Regina et al, 2007), antimalarial (Bader et al, 1969), antileprotic (Dhar, 1975), insecticidal, ascarcidal, analgesic, and hypnotic (Buehler & Masters, 1939) activities. Similarly, amide group owes its importance due to its presence in many synthetic intermediates, biomolecules and active pharmaceutical products (Grbovi c et al, 2018). It is noteworthy that combining the two groups into the same molecule might render important biological properties to the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies on the recently synthesized sulfones have revealed their antifungal (Xu et al, 2011), antiparasitic (Kerr et al, 2009), antimicrobial (Patil et al, 2010), antiviral (La Regina et al, 2007), antimalarial (Bader et al, 1969), antileprotic (Dhar, 1975), insecticidal, ascarcidal, analgesic, and hypnotic (Buehler & Masters, 1939) activities. Similarly, amide group owes its importance due to its presence in many synthetic intermediates, biomolecules and active pharmaceutical products (Grbovi c et al, 2018). It is noteworthy that combining the two groups into the same molecule might render important biological properties to the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, conversion of carboxylic acids to more reactive intermediates would be necessary to obtain amides. [24][25][26][27][28][29][30] Herein, we report the synthesis of a series of novel chiral tripodal receptors based on the formation of amide bonds under microwave irradiation, and an evaluation of their molecular recognition abilities towards a wide range of anions (H 2 PO 4 -, HSO 4…”
Section: Introductionmentioning
confidence: 99%